Physico-chemical quality characteristics of red pitaya (Hylocereus polyrhizus) after postharvest with 1-MCP - Melly Novita; Ahmad, Siti Hajar; Ding, Phebe; Abd Halim, Mohd Ridzwan (2007)
In this study, the effect of 1-MCP on physico-chemical changes of red pitaya during storage at 10c were determined. Fruits harvested at 30 days after anthesis were treated with 1-MCP (0,500 and 1000 nLŁ)for 4 h and stored at 10c. Changes in fruit colour, firmness, soluble solids concentration (SSC) and titratable acidity (TA) were monitored at 0.7, 14, 21 and 28 days of storage. There were significant changes in peel L*,C* and h values of control and 1000nL/L1-MCP-treated fruits. However, there were no significant relationships between peel L*,C* and h values with storage duration in 500 nL/L1-MCP-treated fruits indicating that 500nL/L 1-MCP maintained peel colour of fruit. Fruit-scale values of L* and C* for control fruits showed significant changes whereby the scales turned carker during storage. There were no significant changes in L*, C* and h values of fruit scales treated with 500 and 1000 nL/L of 1-MCP, SSC and TA of fruits treated with 1-MCP. These indicated that quality of red pitaya treated with 500 and 1000 nL/L of 1-MCP were maintained during 28 days of storage. It appeared that fruit peel and scale colour and physico-chemical quality characteristic were maintained in fruits treated with 500 nL/L of 1-MCP.